Instrumental practice and body discomfort: Study with musicians of violin and viola Prática instrumental e desconforto corporal: Um estudo com músicos de violino e viola - Teixeira C.S. (2015)
The positions adopted during the work routines can generate problems of health and possible removals of the professional practice. This way, this study aimed for to identify the complaint of discomfort musculoskeletal in the different corporal areas with the positions adopted during the 11 musicians strings instrumental practices (violin and viola) of an orchestra semi-professional of the South Brazil region. Data collection was carried out in 2011. The postures adopted in the execution of musical routines were identified by means of movies and the identification of pain and/or discomfort by Corlett and Bishop (1976) questionnaire. The largest complaints were related to region of neck, superior leaves of backs, shoulder and left arm. These symptoms can be related to the postures adopted during the instrumental practices, because the largest problems of positions were found in the region of the cervical with improper flexion (72,73%), hypercifosis (81,82%) and in the region of the left shoulder with internal rotation (54,55%) and excessive elevation (54,55%). Those discoveries can elucidate part of the causes of the pains told by the musicians, since in the analyzed postures it identified contractions and unnecessary articulate positions during the whole time of the practice with instrument.